Telomere Biology: Key to unlocking the fountain of youth…A Systematic Review. - Anirban Poddar; Anup Kumar Rana; Ranjita Santra; Phalguni Chakrabarti (Florea : Jurnal Biologi dan Pembelajarannya, 2024)
Advances in medical science has lead to increase in life expectancy of human beings all over the world. Deterioration of physiological functions is typically associated with ageing process.This often manifests as various diseases which eventually creates a burden on health infrastructure.Telomere attrition is a phenomenon which involves shortening of telomeres with each cycle of cell division.The phenomenon of “Telomere Attrition” is a “Bi edged sword” as while being a protective shield for the genome on one hand, it also is the cause of many senility related degenerative disorders. As the role of telomere biology is well established in ageing,current research therefore aims to develop means to reduce telomere attrition,thereby reducing ageing & age related diseases.This review will focus on summarising the role of telomere biology in ageing & age related diseases while highlighting the recent advances in research aiming towards enhanced longevity & healthy ageing.This review will further emphasize on telomere targetted therapeutics such as telomerase activators & tankyrase inhibitors while also highlighting the role of antioxidative & antiinflammatory agents alongwith indirectly related approaches such as statins.